Method for recycling and regenerating positive electrode material of waste lithium battery

Through the disassembly and multi-step recycling of waste lithium batteries, efficient recycling of lithium ions and high-quality regeneration of lithium battery positive electrode materials have been successfully achieved, solving the problems of harmful substances and waste of resources in waste lithium batteries, and improving the cycle life and electrical performance of the battery.

CN119812547AActive Publication Date: 2025-04-11RUICHI NEW ENERGY (XUZHOU) CO LTD

Patent Information

Application Number
CN202510000967.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

Waste lithium batteries contain harmful substances and their metal resource recovery rate is low, resulting in environmental pollution and waste of resources.

Method used

The waste lithium iron phosphate battery was discharged and disassembled, and the current collector was circulated and soaked in hot and cold water. After calcination, lithium ions were selectively leaching with sulfuric acid-hydrogen peroxide, lithium carbonate was recovered, and efficient lithium battery positive electrode material was prepared through co-precipitation and secondary calcination.

Benefits of technology

It realizes efficient recovery of lithium ions and high-quality regeneration of cathode materials, reduces environmental pollution and resource waste, and improves the cycle life and electrical performance of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225110990000121
    Figure BDA0005225110990000121
  • Figure BDA0005225110990000131
    Figure BDA0005225110990000131
  • Figure BDA0005225110990000132
    Figure BDA0005225110990000132
Patent Text Reader

Abstract

The invention discloses a method for recycling a waste lithium battery positive electrode material, and relates to the technical field of lithium battery positive electrode materials. When the lithium battery positive electrode material is prepared, the waste lithium iron phosphate battery is discharged and then disassembled, a current collector is separated through cyclic soaking in cold and hot water, lithium ions are selectively leached through sulfuric acid-hydrogen peroxide after calcination, and the recycled lithium carbonate is obtained through recycling; preparing a carbonic acid ternary precursor by using a coprecipitation method; mixing the carbonic acid ternary precursor, recycled lithium carbonate, silicon monoxide, lithium fluoride and neodymium oxide, and performing secondary calcination to obtain a doped modified ternary positive electrode material; compounding and coating lanthanum, aluminum and zinc on the surface of the doped modified ternary positive electrode material by using a potassium-sodium alloy reduction method to prepare a coated modified ternary positive electrode material; and mixing the coated modified ternary positive electrode material with a conductive agent and a binder, and coating a carbon-coated aluminum foil with the mixture to prepare the lithium battery positive electrode material. The lithium battery positive electrode material prepared by the invention has high charge-discharge specific capacity, long cycle life and good rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium battery positive electrode materials, in particular to a method for recycling waste lithium battery positive electrode materials. Background Art

[0002] With the rapid growth of population and rapid economic development in various countries around the world, modern society has an urgent and significant demand for more sustainable and versatile energy supply. Nowadays, most of the world's energy comes from fossil fuels, which are non-renewable energy sources, which inevitably lead to the emergence of energy crises and increased environmental pollution. Therefore, more sustainable and green energy sources are increasingly valued by people. These energy sources are usually collected from wind energy, solar energy, tides or hydropower in the form of electrical energy. Therefore, various types of batteries, especially lithium-ion batteries, which are based on the principle of reversible insertion and removal of lithium ions in the positive and negative electrodes to store and release electrical energy, have been manufactured and applied on a large scale.

[0003] Power batteries are one of the most core components in the structure of new energy vehicles, accounting for 30% to 40% of the cost of the whole vehicle. The most commonly used power batteries in new energy vehicles are currently two series: nickel-cobalt-manganese ternary batteries with a layered structure and lithium iron phosphate batteries with an olivine structure. Among them, in the early stages of the development of new energy vehicles in my country, lithium iron phosphate batteries were considered to be more promising among various lithium-ion batteries due to their excellent safety performance, sufficiently long cycle life, and lower manufacturing costs compared to other batteries, and were therefore more widely used in various types of commercial buses and family cars. With the continuous increase in the number of years of use, lithium-ion batteries are also getting closer to the retirement deadline. Generally speaking, when the actual capacity of the power battery decays to about 80% of its rated value, it needs to be retired. Due to the widespread popularity of early new energy vehicles, a large number of retired power batteries are about to flood into the market.

[0004] Waste lithium-ion batteries contain a lot of substances that may cause damage to human health and the ecological environment, such as a large amount of heavy metals and electrolyte solutions such as waste acid and waste alkali. The presence of heavy metals in waste lithium-ion batteries, if leaked, will cause pollution of water bodies such as rivers, lakes and oceans, affecting the survival of aquatic organisms and the utilization of natural resources, and indirectly affecting human health. Acids, alkalis and electrolytes in waste may cause soil erosion, causing it to become acidic and salinized. However, it is worth noting that waste lithium batteries themselves contain extremely rich metal resources, such as iron, lithium, aluminum, etc., of which lithium metal elements account for about 1%, which is more than ordinary lithium ore, so it presents a higher recycling value. Therefore, the expiration of the service life of new energy vehicle power batteries does not mean the end of "life", but it may "turn waste into treasure". The recovery of lithium metal elements in waste lithium batteries can not only improve the comprehensive utilization rate of lithium resources, effectively reduce the reserve pressure of lithium resources, but also enhance the sustainability of the development of green industries such as new energy electric vehicles and energy storage power stations. Summary of the invention

[0005] The purpose of the present invention is to provide a method for recycling positive electrode materials of waste lithium batteries to solve the problems existing in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A lithium battery positive electrode material, which is prepared by mixing a coated modified ternary positive electrode material with a conductive agent and a binder and then coating the mixture on a carbon-coated aluminum foil;

[0008] The coated modified ternary positive electrode material is prepared by mixing lanthanum acetylacetonate, zinc acetylacetonate, aluminum acetylacetonate and a doped modified ternary positive electrode material, shearing the mixture at high speed, adding a potassium-sodium alloy for reduction and then calcining the mixture;

[0009] The doped modified ternary positive electrode material is prepared by mixing a ternary carbonate precursor, recycled lithium carbonate, silicon dioxide, lithium fluoride and neodymium oxide and then calcining the mixture twice;

[0010] The lithium carbonate recovery method is to disassemble the waste lithium iron phosphate battery after discharge, immerse the separated current collector in cold and hot water in a cycle, and then calcine and selectively leach lithium ions with sulfuric acid-hydrogen peroxide for recovery;

[0011] The ternary carbonate precursor is prepared by mixing a nickel source, a cobalt source and a manganese source to form a mixed salt solution, and then adding a precipitant solution under the complexation of ammonia water to perform co-precipitation.

[0012] As optimization, the nickel source is nickel sulfate heptahydrate; the cobalt source is cobalt sulfate hexahydrate; and the manganese source is manganese sulfate monohydrate.

[0013] As an optimization, the mixed salt solution is prepared by dissolving a nickel source, a cobalt source, and a manganese source in pure water at a molar ratio of 6:2:2 to form a 2 mol / L mixed salt solution.

[0014] As an optimization, the precipitant solution is prepared by mixing 1 mol / L sodium carbonate solution and 1 mol / L ammonium bicarbonate solution in a volume ratio of 1:1.

[0015] A method for recycling and regenerating waste lithium battery positive electrode materials comprises the following preparation steps:

[0016] (1) manually disassembling the waste lithium iron phosphate battery after discharge and inactivation to separate the lithium iron phosphate positive electrode sheet, soaking the lithium iron phosphate positive electrode sheet in hot water and cold water in turn, soaking for 2 to 3 minutes each time, and immersing in a cycle until the current collector is detached to obtain a lithium iron phosphate positive electrode material, adding dimethylformamide and the lithium iron phosphate positive electrode material at a liquid-solid ratio of 3:1 g / g to mix evenly, calcining at 450 to 500° C. for 2 to 3 hours in an argon atmosphere, naturally cooling to room temperature, crushing and grinding to pass through a 100-mesh sieve, and obtaining a lithium iron phosphate positive electrode material powder;

[0017] (2) According to the mass fraction, 2 to 3 parts of lithium iron phosphate positive electrode material powder, 4 to 6 parts of hydrogen peroxide, 16 to 24 parts of 0.4 mol / L sulfuric acid solution, and 80 to 120 parts of pure water are mixed evenly, stirred at 68 to 72° C. and 250 to 350 r / min for 30 to 40 min, filtered, and the residue is separated for iron recovery. The filtrate is concentrated to a lithium ion concentration of 30 g / L, and the pH is adjusted to 10 with sodium hydroxide solution. Saturated sodium carbonate solution is added at 90° C. and 300 to 400 r / min at a molar ratio of sodium carbonate to lithium ions of (1.2 to 1.4):1. After the addition is completed, stirring is continued for 60 to 80 min, filtered, washed with boiling pure water for 3 to 4 times, and vacuum dried at 70 to 80° C. for 10 to 12 h to obtain recovered lithium carbonate;

[0018] (3) First, add 20 to 30 parts of pure water by mass, and then add 40 to 50 parts of mixed salt solution, 20 to 30 parts of ammonia water, and 50 to 60 parts of precipitant solution at 60 to 70°C and 500 to 600 r / min, and control the flow rate ratio of the mixed salt solution to the ammonia water to be 2:1. Control the flow rate of the precipitant solution to control the pH at 7.5 to 8. After all the additions are completed, react for 8 to 10 hours, stop stirring, seal, age in a water bath at 60 to 70°C for 12 to 14 hours, filter, wash with pure water until the pH is less than 7.5, vacuum dry at 60 to 70°C for 6 to 8 hours, crush and grind, and pass through a 120-mesh sieve to obtain a ternary carbonate precursor;

[0019] (4) According to the mass fraction, 20 to 30 parts of ternary carbonate precursor, 6.39 to 9.39 parts of recovered lithium carbonate, 0.075 to 0.112 parts of silicon dioxide, 0.176 to 0.396 parts of lithium fluoride, and 2.85 to 4.28 parts of neodymium oxide are mixed evenly, added to a ball mill, ground at 50 to 60 r / min for 5 to 6 hours, passed through a 200-mesh sieve, heated to 450 to 500° C. at a heating rate of 3 to 4° C. / min in an oxygen atmosphere, calcined for 4 to 5 hours, cooled naturally to room temperature, passed through a 200-mesh sieve after grinding, and continued to heat to 800 to 850° C. at a heating rate of 3 to 4° C. / min in an oxygen atmosphere for calcination for 16 to 18 hours, cooled naturally to room temperature, and passed through a 325-mesh sieve after grinding to obtain a doped modified ternary positive electrode material;

[0020] (5) By weight, 0.064-0.085 parts of lanthanum acetylacetonate, 0.039-0.051 parts of zinc acetylacetonate, 0.048-0.063 parts of aluminum acetylacetonate, 3-4 parts of doped modified ternary cathode material, and 50-60 parts of ethylene glycol dimethyl ether were mixed uniformly, ultrasonicated for 15-20 minutes, stirred at 1200-1400 r / min for 3-4 minutes in an argon atmosphere, and 0.6-0.8 parts of potassium-sodium alloy were added. , continue stirring for 15 to 20 minutes, centrifuge at 8000 to 10000 rpm for 8 to 10 minutes, wash the solid with ethylene glycol dimethyl ether 2 to 3 times, vacuum dry at 60 to 70 ° C for 6 to 8 hours, crush and grind, pass through a 325-mesh sieve, heat to 800 to 850 ° C at a heating rate of 3 to 4 ° C / min in an air atmosphere, calcine for 4 to 5 hours, cool naturally to room temperature, grind and pass through a 325-mesh sieve to obtain a coated modified ternary positive electrode material;

[0021] (6) The coated modified ternary positive electrode material, conductive agent and binder are mixed in a mass ratio of 8:1:1, poured into a ball mill, stirred for 10 to 15 minutes using a high-speed oscillating ball mill, added with 3.5 times the total mass of N-methylpyrrolidone, stirred at 300 to 400 r / min for 3 to 4 hours, evenly spread on a carbon-coated aluminum foil, vacuum dried at 60°C for 3 to 4 hours, and then vacuum dried at 120°C for 10 to 12 hours to obtain a lithium battery positive electrode material.

[0022] As an optimization, the hot water in step (1) is 80-90°C, and the cold water is 10-20°C.

[0023] As an optimization, the concentration of the hydrogen peroxide in step (2) is 30 wt %.

[0024] As an optimization, the concentration of the sodium hydroxide solution in step (2) is 0.5 mol / L.

[0025] As an optimization, the ammonia concentration in step (3) is 1 mol / L.

[0026] As an optimization, the mass ratio of potassium to sodium in the potassium-sodium alloy in step (5) is 3:1.

[0027] As an optimization, the conductive agent in step (6) is acetylene black, and the median diameter is 1 to 3 μm.

[0028] As an optimization, the binder in step (6) is polyvinylidene fluoride, model number Kynar 741.

[0029] As an optimization, the carbon-coated aluminum foil in step (6) was purchased from Guangzhou Nano New Materials Technology Co., Ltd.

[0030] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0031] When preparing the positive electrode material of a lithium battery, the present invention firstly disassembles the waste lithium iron phosphate battery after discharging, circulates and soaks the separated current collector in cold and hot water, and selectively leaches lithium ions with sulfuric acid-hydrogen peroxide after calcination to recover the recovered lithium carbonate; after mixing a nickel source, a cobalt source and a manganese source to form a mixed salt solution, a precipitant solution is added under the complexation of ammonia water to carry out co-precipitation to obtain a ternary carbonate precursor; after mixing the ternary carbonate precursor, recovered lithium carbonate, silicon dioxide, lithium fluoride and neodymium oxide, the mixture is calcined twice to obtain a doped modified ternary positive electrode material; after mixing lanthanum acetylacetonate, zinc acetylacetonate, aluminum acetylacetonate and the doped modified ternary positive electrode material, high-speed shearing is carried out, potassium sodium alloy is added for reduction and the mixture is calcined to obtain a coated modified ternary positive electrode material; after mixing the coated modified ternary positive electrode material with a conductive agent and a binder, the mixture is coated on a carbon-coated aluminum foil to obtain a lithium battery positive electrode material.

[0032] First, the waste lithium iron phosphate battery is disassembled after discharge, and the current collector is separated by circulating in cold and hot water. After calcination, sulfuric acid-hydrogen peroxide is used to selectively leach lithium ions for recovery to obtain recycled lithium carbonate. After the waste lithium iron phosphate battery is discharged and inactivated, it can be safely disassembled manually. Taking advantage of the large difference in thermal expansion coefficients between the binder and the aluminum foil current collector, the binder is completely separated from the aluminum foil current collector by circulating in cold and hot water, reducing the residual aluminum impurities in the positive electrode material, avoiding the use of chemical reagents, and reducing emissions. Then dimethylformamide is added to assist mixing. After that, high-temperature calcination is carried out to completely remove impurities such as the binder in the positive electrode material, retain the complete positive electrode active material, and then leaching is carried out with a sulfuric acid-hydrogen peroxide system. The parameters are optimized so that the leaching rate of lithium ions reaches more than 98%, while the leaching rate of iron ions is less than 0.5%. The iron element is enriched in the filter residue, and the iron element can be recovered later. The lithium ions in the filtrate are concentrated and recovered by precipitation with sodium carbonate. The first precipitation rate is greater than 89%, and the purity of the recovered lithium carbonate is greater than 99.5%, which meets the battery grade standard and can be used for the subsequent regeneration preparation of positive electrode materials.

[0033] Secondly, the nickel source, cobalt source and manganese source are mixed into a mixed salt solution, and then a precipitant solution is added under the complexation of ammonia water to perform co-precipitation to obtain a carbonate ternary precursor. The mixed salt solution of the nickel source, cobalt source and manganese source is added in parallel with ammonia water and a precipitant solution to optimize the nucleation and crystallization path of the precipitation, which can improve the electrical properties of the lithium battery positive electrode material prepared subsequently. At the same time, as for the precipitant solution, a sodium carbonate solution is not used alone, but a mixed solution of sodium carbonate and ammonium bicarbonate is used. The pH of the simple sodium carbonate solution is greater than the pH of the mixed solution of sodium carbonate and ammonium bicarbonate, which will cause nickel hydroxide to appear in the precursor. The impurity phase leads to the decline of the electrical performance of the subsequent lithium battery positive electrode material; the carbonate ternary precursor, recycled lithium carbonate, silicon oxide, lithium fluoride, and neodymium oxide are mixed and calcined twice to obtain a doped modified ternary positive electrode material. Silicon oxide, lithium fluoride, and neodymium oxide are mixed during high-temperature calcination to dope fluorine, silicon, and neodymium elements into the lithium battery positive electrode material. The doping of neodymium element inhibits the mixing of lithium and nickel, increases the lattice spacing, expands the lithium ion transmission channel, reduces the lithium ion deintercalation barrier and accelerates electron migration. At the same time, the doping of fluorine further increases the inhibitory effect on the mixing of lithium and nickel. At the same time, the electronegativity of fluorine is stronger than that of oxygen. The strength of the lithium-fluorine bond is greater, the crystal configuration is more stable during repeated charge and discharge, and the cycle performance is also improved. The doped fluorine can also inhibit the damage of hydrofluoric acid in the electrolyte to the positive electrode material to a certain extent, and the trace doping of silicon further expands the lattice spacing, which is conducive to the rapid migration of lithium ions. At the same time, the doping of silicon regulates the radial growth of the primary calcined particles, showing an elongated nano-needle structure. The spherical secondary particles stacked thereby are conducive to reducing the concentration of interfacial stress, and increasing the transmission rate of lithium ions, improving electrical properties, and at the same time, the doping of silicon is conducive to resisting the corrosion of the electrolyte. And delay the collapse of the crystal structure. In the co-doping of fluorine, silicon and neodymium, on the one hand, the strong electronegativity of fluorine ions and the supporting synergy of silicon and neodymium make the structural stability better during the charging and discharging process. On the other hand, in order to balance the increase in valence caused by the composite doping of fluorine ions and neodymium ions, the number of low-valent transition metal ions is increased, the unit cell volume is increased, the diffusion channel of lithium ions is expanded, and the electrical properties are improved. In the calcination process, the secondary calcination method is used, first pre-burning at a low temperature and then grinding, so that the metal elements are further evenly mixed, the regularity of crystal growth is improved, which is beneficial to the improvement of electrical properties.

[0034] Finally, lanthanum acetylacetonate, zinc acetylacetonate, aluminum acetylacetonate and doped modified ternary positive electrode materials are mixed and sheared at high speed, and potassium sodium alloy is added for reduction and calcined to obtain coated modified ternary positive electrode materials. The high reducibility of potassium sodium alloy is utilized to jointly coat lanthanum, zinc and aluminum elements on the surface of doped modified ternary positive electrode materials. At the same time, the high-speed shear force is utilized to make the coating more uniform. At the same time, the process conditions are simple and controllable. The obtained lanthanum, zinc and aluminum composite oxide coating layer can effectively reduce the corrosion of electrolyte on positive electrode materials, reduce the occurrence of side reactions, protect the integrity and regularity of materials, and effectively extend the cycle life. At the same time, the coating layer of multiple metal oxides can give full play to the synergistic effect between transition metals, on the one hand, promote the permeation of ions and electrons and increase the conductivity, and on the other hand, effectively weaken the interface impedance and improve the rate performance. The coated modified ternary positive electrode material is mixed with a conductive agent and a binder and then coated on a carbon-coated aluminum foil to obtain a lithium battery positive electrode material. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] Embodiment 1:

[0037] A method for recycling positive electrode materials of waste lithium batteries, the method comprising the following preparation steps:

[0038] (1) manually disassembling the waste lithium iron phosphate battery after discharge and inactivation to separate the lithium iron phosphate positive electrode sheet, soaking the lithium iron phosphate positive electrode sheet in 80° C. hot water and 20° C. cold water in turn, soaking for 3 minutes each time, and immersing in a cycle until the current collector is detached to obtain a lithium iron phosphate positive electrode material, adding dimethylformamide and the lithium iron phosphate positive electrode material at a liquid-solid ratio of 3:1 g / g to mix evenly, calcining at 450° C. for 3 hours under an argon atmosphere, naturally cooling to room temperature, crushing and grinding to pass through a 100-mesh sieve, and obtaining a lithium iron phosphate positive electrode material powder;

[0039] (2) According to the mass fraction, 2 parts of lithium iron phosphate positive electrode material powder, 4 parts of hydrogen peroxide, 16 parts of 0.4 mol / L sulfuric acid solution, and 80 parts of pure water were mixed evenly, stirred at 68°C and 250 r / min for 40 min, filtered, and the residue was separated for iron recovery. The filtrate was concentrated to a lithium ion concentration of 30 g / L, and the pH was adjusted to 10 with sodium hydroxide solution. Saturated sodium carbonate solution was added at 90°C and 300 r / min at a molar ratio of sodium carbonate to lithium ions of 1.2:1. After the addition was completed, stirring was continued for 80 min, filtered, washed with boiling pure water for 3 times, and vacuum dried at 70°C for 12 h to obtain recovered lithium carbonate;

[0040] (3) First, add 20 parts of pure water by mass, then add 40 parts of mixed salt solution, 20 parts of ammonia water, and 50 parts of precipitant solution at 60°C and 500 r / min, control the flow rate ratio of the mixed salt solution and ammonia water to be 2:1, control the flow rate of the precipitant solution to control the pH at 7.5, react for 8 hours after all are added, stop stirring, seal and age in a 60°C water bath for 14 hours, filter, wash with pure water until the pH is less than 7.5, vacuum dry at 60°C for 8 hours, crush and grind, and pass through a 120-mesh sieve to obtain a ternary carbonate precursor;

[0041] (4) According to the mass fraction, 20 parts of carbonate ternary precursor, 6.39 parts of recycled lithium carbonate, 0.075 parts of silicon dioxide, 0.176 parts of lithium fluoride, and 2.85 parts of neodymium oxide were mixed evenly, added to a ball mill, ground at 50 r / min for 6 h, passed through a 200-mesh sieve, heated to 450° C. at a heating rate of 3° C. / min in an oxygen atmosphere, calcined for 5 h, cooled naturally to room temperature, and passed through a 200-mesh sieve after grinding. In an oxygen atmosphere, the temperature was continuously increased to 800° C. at a heating rate of 3° C. / min and calcined for 18 h. The mixture was naturally cooled to room temperature, and passed through a 325-mesh sieve after grinding to obtain a doped modified ternary positive electrode material;

[0042] (5) By weight, 0.064 parts of lanthanum acetylacetonate, 0.039 parts of zinc acetylacetonate, 0.048 parts of aluminum acetylacetonate, 3 parts of doped modified ternary cathode material, and 50 parts of ethylene glycol dimethyl ether were mixed uniformly, ultrasonicated for 15 minutes, stirred at 1200 r / min for 4 minutes under an argon atmosphere, 0.6 parts of potassium sodium alloy were added, and stirring was continued for 15 minutes. The solid was centrifuged at 8000 rpm for 10 minutes, and the solid was washed twice with ethylene glycol dimethyl ether, vacuum dried at 60°C for 8 hours, crushed and ground, and passed through a 325-mesh sieve. In an air atmosphere, the temperature was increased to 800°C at a heating rate of 3°C / min and calcined for 5 hours. The mixture was naturally cooled to room temperature, ground and passed through a 325-mesh sieve to obtain a coated modified ternary cathode material;

[0043] (6) The coated modified ternary positive electrode material, conductive agent and binder were mixed in a mass ratio of 8:1:1, poured into a ball mill, stirred for 10 minutes using a high-speed oscillating ball mill, added with 3.5 times the total mass of N-methylpyrrolidone, stirred at 300 r / min for 4 hours, evenly spread on a carbon-coated aluminum foil, vacuum dried at 60°C for 3 hours, and then vacuum dried at 120°C for 10 hours to obtain a lithium battery positive electrode material.

[0044] Embodiment 2:

[0045] A method for recycling positive electrode materials of waste lithium batteries, the method comprising the following preparation steps:

[0046] (1) manually disassembling the waste lithium iron phosphate battery after discharge and inactivation to separate the lithium iron phosphate positive electrode sheet, soaking the lithium iron phosphate positive electrode sheet in 85° C. hot water and 15° C. cold water in turn, soaking for 2.5 minutes each time, and immersing in a cycle until the current collector is detached to obtain a lithium iron phosphate positive electrode material, adding dimethylformamide and the lithium iron phosphate positive electrode material at a liquid-solid ratio of 3:1 g / g to mix evenly, calcining at 475° C. for 2.5 hours under an argon atmosphere, naturally cooling to room temperature, crushing and grinding to pass through a 100-mesh sieve, and obtaining a lithium iron phosphate positive electrode material powder;

[0047] (2) According to the mass fraction, 2.5 parts of lithium iron phosphate positive electrode material powder, 5 parts of hydrogen peroxide, 20 parts of 0.4 mol / L sulfuric acid solution, and 100 parts of pure water were mixed evenly, stirred at 70°C and 300 r / min for 35 min, filtered, and the residue was separated for iron recovery. The filtrate was concentrated to a lithium ion concentration of 30 g / L, and the pH was adjusted to 10 with sodium hydroxide solution. Saturated sodium carbonate solution was added at 90°C and 350 r / min at a molar ratio of sodium carbonate to lithium ions of 1.3:1. After the addition was completed, stirring was continued for 70 min, filtered, washed with boiling pure water for 3 times, and vacuum dried at 75°C for 11 h to obtain recovered lithium carbonate;

[0048] (3) First, add 25 parts of pure water by mass, then add 45 parts of mixed salt solution, 25 parts of ammonia water, and 55 parts of precipitant solution at 65°C and 550 r / min, control the flow rate ratio of the mixed salt solution to the ammonia water to be 2:1, control the flow rate of the precipitant solution to control the pH at 7.8, react for 9 hours after all are added, stop stirring, seal and age in a water bath at 65°C for 13 hours, filter, wash with pure water until the pH is less than 7.5, vacuum dry at 65°C for 7 hours, crush and grind, and pass through a 120-mesh sieve to obtain a ternary carbonate precursor;

[0049] (4) According to the mass fraction, 25 parts of carbonate ternary precursor, 7.91 parts of recovered lithium carbonate, 0.093 parts of silicon dioxide, 0.275 parts of lithium fluoride, and 3.56 parts of neodymium oxide were mixed evenly, added to a ball mill, ground at 55 r / min for 5.5 h, passed through a 200-mesh sieve, heated to 475° C. at a heating rate of 4° C. / min in an oxygen atmosphere, calcined for 4.5 h, cooled naturally to room temperature, passed through a 200-mesh sieve after grinding, and continued to heat to 825° C. at a heating rate of 4° C. / min in an oxygen atmosphere for 17 h. Cooled naturally to room temperature, and passed through a 325-mesh sieve after grinding to obtain a doped modified ternary positive electrode material;

[0050] (5) By weight, 0.075 parts of lanthanum acetylacetonate, 0.045 parts of zinc acetylacetonate, 0.055 parts of aluminum acetylacetonate, 3.5 parts of doped modified ternary cathode material, and 55 parts of ethylene glycol dimethyl ether were mixed uniformly, ultrasonicated for 18 minutes, stirred at 1300 r / min for 3.5 minutes in an argon atmosphere, 0.7 parts of potassium sodium alloy were added, and stirring was continued for 18 minutes. The solid was centrifuged at 9000 rpm for 9 minutes, and the solid was washed with ethylene glycol dimethyl ether for 3 times, vacuum dried at 65°C for 7 hours, crushed and ground, and passed through a 325-mesh sieve. In an air atmosphere, the temperature was increased to 825°C at a heating rate of 4°C / min and calcined for 4.5 hours, cooled naturally to room temperature, ground and passed through a 325-mesh sieve to obtain a coated modified ternary cathode material;

[0051] (6) The coated modified ternary positive electrode material, conductive agent and binder were mixed in a mass ratio of 8:1:1, poured into a ball mill, stirred for 12 minutes using a high-speed oscillating ball mill, added with 3.5 times the total mass of N-methylpyrrolidone, stirred at 350 r / min for 3.5 hours, evenly spread on a carbon-coated aluminum foil, vacuum dried at 60°C for 3.5 hours, and then vacuum dried at 120°C for 11 hours to obtain a lithium battery positive electrode material.

[0052] Embodiment 3:

[0053] A method for recycling positive electrode materials of waste lithium batteries, the method comprising the following preparation steps:

[0054] (1) manually disassembling the waste lithium iron phosphate battery after discharge and inactivation to separate the lithium iron phosphate positive electrode sheet, soaking the lithium iron phosphate positive electrode sheet in 90° C. hot water and 10° C. cold water in turn, soaking for 2 minutes each time, and immersing in a cycle until the current collector is detached to obtain a lithium iron phosphate positive electrode material, adding dimethylformamide and the lithium iron phosphate positive electrode material at a liquid-solid ratio of 3:1 g / g to mix evenly, calcining at 500° C. for 2 hours under an argon atmosphere, naturally cooling to room temperature, crushing and grinding to pass through a 100-mesh sieve, and obtaining a lithium iron phosphate positive electrode material powder;

[0055] (2) By weight, 3 parts of lithium iron phosphate positive electrode material powder, 6 parts of hydrogen peroxide, 24 parts of 0.4 mol / L sulfuric acid solution, and 120 parts of pure water were mixed evenly, stirred at 72°C and 350 r / min for 30 min, filtered, and the residue was separated for iron recovery. The filtrate was concentrated to a lithium ion concentration of 30 g / L, and the pH was adjusted to 10 with sodium hydroxide solution. Saturated sodium carbonate solution was added at 90°C and 400 r / min at a molar ratio of sodium carbonate to lithium ions of 1.4:1. After the addition was completed, stirring was continued for 60 min, filtered, washed with boiling pure water 4 times, and vacuum dried at 80°C for 10 h to obtain recovered lithium carbonate;

[0056] (3) First, add 30 parts of pure water by mass, then add 50 parts of mixed salt solution, 30 parts of ammonia water, and 60 parts of precipitant solution at 70°C and 600 r / min, control the flow rate ratio of the mixed salt solution and ammonia water to be 2:1, control the flow rate of the precipitant solution to control the pH at 8, react for 10 hours after all are added, stop stirring, seal and age in a 70°C water bath for 12 hours, filter, wash with pure water until the pH is less than 7.5, vacuum dry at 70°C for 6 hours, crush and grind, and pass through a 120-mesh sieve to obtain a ternary carbonate precursor;

[0057] (4) By weight, 30 parts of ternary carbonate precursor, 9.39 parts of recovered lithium carbonate, 0.112 parts of silicon dioxide, 0.396 parts of lithium fluoride, and 4.28 parts of neodymium oxide were mixed evenly, added to a ball mill, ground at 60 r / min for 5 h, passed through a 200-mesh sieve, heated to 500° C. at a heating rate of 4° C. / min in an oxygen atmosphere, calcined for 4 h, naturally cooled to room temperature, and passed through a 200-mesh sieve after grinding. In an oxygen atmosphere, the temperature was continued to be increased to 850° C. at a heating rate of 4° C. / min and calcined for 16 h, naturally cooled to room temperature, and passed through a 325-mesh sieve after grinding to obtain a doped modified ternary positive electrode material;

[0058] (5) By weight, 0.085 parts of lanthanum acetylacetonate, 0.051 parts of zinc acetylacetonate, 0.063 parts of aluminum acetylacetonate, 4 parts of doped modified ternary cathode material, and 60 parts of ethylene glycol dimethyl ether were mixed uniformly, ultrasonicated for 20 minutes, stirred at 1400 r / min for 3 minutes under an argon atmosphere, 0.8 parts of potassium sodium alloy were added, and stirring was continued for 20 minutes. The solid was centrifuged at 10000 rpm for 8 minutes, and the solid was washed with ethylene glycol dimethyl ether for 3 times, vacuum dried at 70°C for 6 hours, crushed and ground, and passed through a 325-mesh sieve. In an air atmosphere, the temperature was increased to 850°C at a heating rate of 4°C / min and calcined for 4 hours. The mixture was naturally cooled to room temperature, ground and passed through a 325-mesh sieve to obtain a coated modified ternary cathode material;

[0059] (6) The coated modified ternary positive electrode material, conductive agent and binder were mixed in a mass ratio of 8:1:1, poured into a ball mill, stirred for 15 minutes using a high-speed oscillating ball mill, added with 3.5 times the total mass of N-methylpyrrolidone, stirred at 400 r / min for 3 hours, evenly spread on a carbon-coated aluminum foil, vacuum dried at 60°C for 4 hours, and then vacuum dried at 120°C for 12 hours to obtain a lithium battery positive electrode material.

[0060] Comparative Example 1:

[0061] The difference between the method for recycling and regenerating the positive electrode material of waste lithium batteries in Comparative Example 1 and Example 2 lies in the difference in step (3), which is modified as follows: by mass, 25 parts of pure water are first added, at 65°C, 550r / min, 45 parts of mixed salt solution are first added, 25 parts of ammonia water are added dropwise at a rate of 2 drops per second, stirring is continued for 30 minutes after the addition is completed, and then a precipitant solution is added dropwise at a rate of one drop per 4 seconds to adjust the pH to 7.8, and the reaction is carried out for 9 hours after all additions are completed, stirring is stopped, and the mixture is sealed and aged in a water bath at 65°C for 13 hours, filtered, washed with pure water until the pH is less than 7.5, vacuum dried at 65°C for 7 hours, crushed and ground, and passed through a 120-mesh sieve to obtain a ternary carbonate precursor. The remaining steps are the same as those in Example 2.

[0062] Comparative Example 2:

[0063] The difference between the method for recycling and regenerating the positive electrode material of waste lithium batteries in Comparative Example 2 and that in Example 2 is that the precipitant used in step (3) is a 1 mol / L sodium carbonate solution. The remaining steps are the same as those in Example 2.

[0064] Comparative Example 3:

[0065] The difference between the method for recycling and regenerating the waste lithium battery positive electrode material of Comparative Example 3 and Example 2 lies in the difference in step (4), and step (4) is modified as follows: by mass, 25 parts of carbonate ternary precursor, 7.91 parts of recovered lithium carbonate, 0.093 parts of silicon dioxide, 0.275 parts of lithium fluoride, and 3.56 parts of neodymium oxide are mixed evenly, added to a ball mill, ground at 55r / min for 5.5h, passed through a 200-mesh sieve, heated to 475°C at a heating rate of 4°C / min in an oxygen atmosphere, calcined for 4.5h, and continued to heat to 825°C at a heating rate of 4°C / min for 17h, cooled naturally to room temperature, and passed through a 325-mesh sieve after grinding to obtain a doped modified ternary positive electrode material. The remaining steps are the same as in Example 2.

[0066] Comparative Example 4:

[0067] The difference between the method for recycling and regenerating the waste lithium battery positive electrode material of Comparative Example 4 and Example 2 lies in the difference in step (4), and step (4) is modified as follows: by mass, 25 parts of ternary carbonate precursor, 7.91 parts of recovered lithium carbonate, 0.093 parts of silicon dioxide, 0.275 parts of lithium fluoride, and 3.56 parts of neodymium oxide are mixed evenly, added to a ball mill, ground at 55r / min for 5.5h, passed through a 200-mesh sieve, heated to 825°C at a heating rate of 4°C / min in an oxygen atmosphere, calcined for 20h, naturally cooled to room temperature, and passed through a 325-mesh sieve after grinding to obtain a doped modified ternary positive electrode material. The remaining steps are the same as in Example 2.

[0068] Comparative Example 5:

[0069] The difference between the method for recycling and regenerating the waste lithium battery positive electrode material of Comparative Example 5 and Example 2 lies in the difference in step (4), and step (4) is modified as follows: by mass, 25 parts of carbonate ternary precursor, 7.91 parts of recovered lithium carbonate, 0.275 parts of lithium fluoride, and 3.56 parts of neodymium oxide are mixed evenly, added to a ball mill, ground at 55r / min for 5.5h, passed through a 200-mesh sieve, heated to 475°C at a heating rate of 4°C / min in an oxygen atmosphere, calcined for 4.5h, naturally cooled to room temperature, passed through a 200-mesh sieve after grinding, and continued to heat to 825°C at a heating rate of 4°C / min in an oxygen atmosphere, calcined for 17h, naturally cooled to room temperature, and passed through a 325-mesh sieve after grinding to obtain a doped modified ternary positive electrode material. The remaining steps are the same as in Example 2.

[0070] Comparative Example 6:

[0071] The difference between the method for recycling and regenerating the waste lithium battery positive electrode material of Comparative Example 6 and Example 2 lies in the difference in step (4), and step (4) is modified as follows: by mass, 25 parts of carbonate ternary precursor, 7.91 parts of recovered lithium carbonate, and 0.275 parts of lithium fluoride are mixed evenly, added to a ball mill, ground at 55r / min for 5.5h, passed through a 200-mesh sieve, heated to 475°C at a heating rate of 4°C / min in an oxygen atmosphere, calcined for 4.5h, naturally cooled to room temperature, passed through a 200-mesh sieve after grinding, and continued to heat to 825°C at a heating rate of 4°C / min in an oxygen atmosphere, calcined for 17h, naturally cooled to room temperature, and passed through a 325-mesh sieve after grinding to obtain a doped modified ternary positive electrode material. The remaining steps are the same as in Example 2.

[0072] Comparative Example 7:

[0073] The difference between the method for recycling and regenerating the positive electrode material of waste lithium batteries in Comparative Example 7 and Example 2 lies in the difference in step (4), which is modified as follows: 25 parts of ternary carbonate precursor and 8.3 parts of recovered lithium carbonate are mixed uniformly by mass, added to a ball mill, ground at 55r / min for 5.5h, passed through a 200-mesh sieve, heated to 475°C at a heating rate of 4°C / min in an oxygen atmosphere, calcined for 4.5h, naturally cooled to room temperature, passed through a 200-mesh sieve after grinding, and continued to heat to 825°C at a heating rate of 4°C / min in an oxygen atmosphere, calcined for 17h, naturally cooled to room temperature, and passed through a 325-mesh sieve after grinding to obtain a ternary positive electrode material. In step (5), the reaction raw material doped modified ternary positive electrode material is modified to a ternary positive electrode material. The remaining steps are the same as in Example 2.

[0074] Comparative Example 8:

[0075] The difference between the method for recycling and regenerating the cathode material of waste lithium batteries in Comparative Example 8 and that in Example 2 lies in the difference in step (5), where step (5) is modified as follows: by mass, 0.078 parts of zinc acetylacetonate, 0.097 parts of aluminum acetylacetonate, 3.5 parts of doped modified ternary cathode material, and 55 parts of ethylene glycol dimethyl ether are mixed uniformly, ultrasonicated for 18 minutes, stirred at 1300r / min for 3.5 minutes under an argon atmosphere, 0.7 parts of potassium sodium alloy are added, stirred for 18 minutes, centrifuged at 9000rpm for 9 minutes, the solid is washed 3 times with ethylene glycol dimethyl ether, vacuum dried at 65°C for 7 hours, crushed and ground, passed through a 325-mesh sieve, heated to 825°C at a heating rate of 4°C / min in an air atmosphere, calcined for 4.5 hours, cooled naturally to room temperature, ground and passed through a 325-mesh sieve to obtain a coated modified ternary cathode material. The remaining steps are the same as in Example 2.

[0076] Comparative Example 9:

[0077] The difference between the method for recycling and regenerating the waste lithium battery positive electrode material of Comparative Example 9 and Example 2 is that step (5) is not performed, and step (5) is modified as follows: by mass, 0.175 parts of lanthanum acetylacetonate, 3.5 parts of doped modified ternary positive electrode material, and 55 parts of ethylene glycol dimethyl ether are mixed uniformly, ultrasonicated for 18 minutes, stirred at 1300r / min for 3.5 minutes under an argon atmosphere, 0.7 parts of potassium sodium alloy are added, and stirring is continued for 18 minutes, centrifuged at 9000rpm for 9 minutes, the solid is washed 3 times with ethylene glycol dimethyl ether, vacuum dried at 65°C for 7 hours, crushed and ground, passed through a 325-mesh sieve, heated to 825°C at a heating rate of 4°C / min in an air atmosphere, calcined for 4.5 hours, naturally cooled to room temperature, ground and passed through a 325-mesh sieve to obtain a coated modified ternary positive electrode material. The remaining steps are the same as in Example 2.

[0078] Comparative Example 10:

[0079] The method for recycling and regenerating waste lithium battery positive electrode materials in Comparative Example 10 is different from that in Example 2 in that step (5) is not performed, and step (6) is modified as follows: the doped modified ternary positive electrode material, the conductive agent, and the binder are mixed uniformly in a mass ratio of 8:1:1, poured into a ball mill, stirred for 12 minutes using a high-speed swing ball mill, 3.5 times the total mass of N-methylpyrrolidone is added, stirred at 350 r / min for 3.5 hours, evenly applied on a carbon-coated aluminum foil, vacuum dried at 60° C. for 3.5 hours, and then vacuum dried at 120° C. for 11 hours to obtain a lithium battery positive electrode material. The remaining steps are the same as in Example 2.

[0080] The half-cell assembly method used in the subsequent test cases is as follows:

[0081] The prepared lithium battery positive electrode material was cut into a 10 mm diameter round electrode with a flat edge using a punching machine. The remaining materials were assembled into button-type half-cells according to GB / T 43093-2023 for subsequent testing.

[0082] Test Example 1:

[0083] First charge and discharge specific capacity test: Use a current density of 0.1C for the first charge and discharge specific capacity test, define 1C as 200mAh / g, charge at constant current to 4.8V, discharge at constant current to 2.5V, and record the data.

[0084] The results are shown in Table 1.

[0085] Table 1

[0086]

[0087]

[0088] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 10 in Table 1, it can be found that the lithium battery positive electrode material prepared by the present invention has a higher charge and discharge specific capacity and good coulombic efficiency.

[0089] By comparing the data in the table, it is shown that the use of mixed reagents by adding all raw materials and precipitant solution in parallel in the co-precipitation step effectively improves the charge-discharge specific capacity. Compared with step-by-step calcination and direct calcination, the secondary calcination can better improve the crystal structure of the material, thereby improving the charge-discharge specific capacity. At the same time, the co-doping of silicon, fluorine and neodymium also improves the charge-discharge specific capacity, improves the lithium ion diffusion efficiency, expands the lattice spacing, and inhibits the mixing of lithium and nickel, thereby improving the electrical performance.

[0090] Test Example 2:

[0091] Cycle performance test: Use a current density of 0.5C to test the cycle performance of the positive electrode material of the lithium battery, define 1C as 200mAh / g, and cycle 2000 times at room temperature. Take the discharge specific capacity of the battery at a current density of 0.5C in Test Example 3 as a reference, record the discharge specific capacity and capacity retention rate after 2000 cycles, and record the data.

[0092] The results are shown in Table 2.

[0093] Table 2

[0094]

[0095]

[0096] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 10 in Table 2, it can be found that the lithium battery positive electrode material prepared by the present invention has a good cycle life.

[0097] By comparing the data in the table, it is shown that the use of mixed reagents in the co-precipitation step by adding all raw materials and the precipitant solution in parallel can effectively improve the crystal structure and growth shape, and effectively improve the cycle life. Compared with step-by-step calcination and direct calcination, the secondary calcination can better improve the crystal structure of the material, thereby improving the cycle life. The co-doping of silicon, fluorine and neodymium improves the lithium ion diffusion efficiency, expands the lattice spacing, and inhibits the mixing of lithium and nickel, thereby improving the cycle life. The presence of the composite coating layer effectively extends the cycle life by blocking the corrosion of the electrolyte to the positive electrode material and reducing the occurrence of side reactions.

[0098] Test Example 3:

[0099] Rate performance test: At room temperature, use current densities of 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, and 10C for 5 cycles respectively, defining 1C as 200mAh / g, to test the rate performance of the lithium battery positive electrode material and record the data.

[0100] The results are shown in Table 3.

[0101] Table 3

[0102]

[0103]

[0104] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 10 in Table 3, it can be found that the lithium battery positive electrode material prepared by the present invention has good rate performance.

[0105] By comparing the data in the table, it can be seen that both doping modification and coating modification effectively improve the rate performance of lithium battery positive electrode materials. The coating layer improves the rate performance by increasing the electrical conductivity and reducing the interface impedance, while the doping modification improves the rate performance by maintaining the structural integrity. Both effectively improve the rate performance of the positive electrode materials.

[0106] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A positive electrode material for a lithium battery, characterized in that: The lithium battery positive electrode material is prepared by mixing the coated modified ternary positive electrode material with a conductive agent and a binder and then coating the mixture on a carbon-coated aluminum foil; The coated modified ternary positive electrode material is prepared by mixing lanthanum acetylacetonate, zinc acetylacetonate, aluminum acetylacetonate and a doped modified ternary positive electrode material, shearing the mixture at high speed, adding a potassium-sodium alloy for reduction and then calcining the mixture; The doped modified ternary positive electrode material is prepared by mixing a ternary carbonate precursor, recycled lithium carbonate, silicon dioxide, lithium fluoride and neodymium oxide and then calcining the mixture twice; The lithium carbonate recovery method is to disassemble the waste lithium iron phosphate battery after discharge, immerse the separated current collector in cold and hot water in a cycle, and then calcine and selectively leach lithium ions with sulfuric acid-hydrogen peroxide for recovery; The ternary carbonate precursor is prepared by mixing a nickel source, a cobalt source and a manganese source to form a mixed salt solution, and then adding a precipitant solution under the complexation of ammonia water to perform co-precipitation.

2. A lithium battery positive electrode material according to claim 1, characterized in that: The nickel source is nickel sulfate heptahydrate; the cobalt source is cobalt sulfate hexahydrate; and the manganese source is manganese sulfate monohydrate.

3. A lithium battery positive electrode material according to claim 1, characterized in that: The mixed salt solution is prepared by dissolving a nickel source, a cobalt source and a manganese source in pure water at a molar ratio of 6:2:2 to form a 2 mol / L mixed salt solution.

4. A lithium battery positive electrode material according to claim 1, characterized in that: The precipitant solution is prepared by mixing 1 mol / L sodium carbonate solution and 1 mol / L ammonium bicarbonate solution in a volume ratio of 1:

1.

5. A method for recycling positive electrode materials of waste lithium batteries, characterized in that: The method comprises the following preparation steps: (1) manually disassembling the waste lithium iron phosphate battery after discharge and inactivation to separate the lithium iron phosphate positive electrode sheet, soaking the lithium iron phosphate positive electrode sheet in hot water and cold water in turn, soaking for 2 to 3 minutes each time, and immersing in a cycle until the current collector is detached to obtain a lithium iron phosphate positive electrode material, adding dimethylformamide and the lithium iron phosphate positive electrode material at a liquid-solid ratio of 3:1 g / g to mix evenly, calcining at 450 to 500° C. for 2 to 3 hours in an argon atmosphere, naturally cooling to room temperature, crushing and grinding to pass through a 100-mesh sieve, and obtaining a lithium iron phosphate positive electrode material powder; (2) According to the mass fraction, 2 to 3 parts of lithium iron phosphate positive electrode material powder, 4 to 6 parts of hydrogen peroxide, 16 to 24 parts of 0.4 mol / L sulfuric acid solution, and 80 to 120 parts of pure water are mixed evenly, stirred at 68 to 72° C. and 250 to 350 r / min for 30 to 40 min, filtered, and the residue is separated for iron recovery. The filtrate is concentrated to a lithium ion concentration of 30 g / L, and the pH is adjusted to 10 with sodium hydroxide solution. Saturated sodium carbonate solution is added at 90° C. and 300 to 400 r / min at a molar ratio of sodium carbonate to lithium ions of (1.2 to 1.4):

1. After the addition is completed, stirring is continued for 60 to 80 min, filtered, washed with boiling pure water for 3 to 4 times, and vacuum dried at 70 to 80° C. for 10 to 12 h to obtain recovered lithium carbonate; (3) First, add 20 to 30 parts of pure water by mass, then add 40 to 50 parts of mixed salt solution, 20 to 30 parts of ammonia water, and 50 to 60 parts of precipitant solution at 60 to 70°C and 500 to 600 r / min. The flow rate ratio of the mixed salt solution and ammonia solution is controlled to be 2:1, and the flow rate of the precipitant solution is controlled to control the pH value to 7.5-8. After all the solution is added, the reaction is carried out for 8-10 hours, and stirring is stopped. After sealing, the solution is aged in a water bath at 60-70° C. for 12-14 hours, filtered, washed with pure water until the pH value is less than 7.5, vacuum dried at 60-70° C. for 6-8 hours, crushed and ground, and passed through a 120-mesh sieve to obtain a ternary carbonate precursor. (4) According to the mass fraction, 20 to 30 parts of ternary carbonate precursor, 6.39 to 9.39 parts of recovered lithium carbonate, 0.075 to 0.112 parts of silicon dioxide, 0.176 to 0.396 parts of lithium fluoride, and 2.85 to 4.28 parts of neodymium oxide are mixed evenly, added to a ball mill, ground at 50 to 60 r / min for 5 to 6 hours, passed through a 200-mesh sieve, heated to 450 to 500° C. at a heating rate of 3 to 4° C. / min in an oxygen atmosphere, calcined for 4 to 5 hours, cooled naturally to room temperature, passed through a 200-mesh sieve after grinding, and continued to heat to 800 to 850° C. at a heating rate of 3 to 4° C. / min in an oxygen atmosphere for calcination for 16 to 18 hours, cooled naturally to room temperature, and passed through a 325-mesh sieve after grinding to obtain a doped modified ternary positive electrode material; (5) By weight, 0.064-0.085 parts of lanthanum acetylacetonate, 0.039-0.051 parts of zinc acetylacetonate, 0.048-0.063 parts of aluminum acetylacetonate, 3-4 parts of doped modified ternary cathode material, and 50-60 parts of ethylene glycol dimethyl ether were mixed uniformly, ultrasonicated for 15-20 minutes, stirred at 1200-1400 r / min for 3-4 minutes in an argon atmosphere, and 0.6-0.8 parts of potassium-sodium alloy were added. , continue stirring for 15 to 20 minutes, centrifuge at 8000 to 10000 rpm for 8 to 10 minutes, wash the solid with ethylene glycol dimethyl ether 2 to 3 times, vacuum dry at 60 to 70 ° C for 6 to 8 hours, crush and grind, pass through a 325-mesh sieve, heat to 800 to 850 ° C at a heating rate of 3 to 4 ° C / min in an air atmosphere, calcine for 4 to 5 hours, cool naturally to room temperature, grind and pass through a 325-mesh sieve to obtain a coated modified ternary positive electrode material; (6) The coated modified ternary positive electrode material, conductive agent and binder are mixed in a mass ratio of 8:1:1, poured into a ball mill, stirred for 10 to 15 minutes using a high-speed oscillating ball mill, added with 3.5 times the total mass of N-methylpyrrolidone, stirred at 300 to 400 r / min for 3 to 4 hours, evenly spread on a carbon-coated aluminum foil, vacuum dried at 60°C for 3 to 4 hours, and then vacuum dried at 120°C for 10 to 12 hours to obtain a lithium battery positive electrode material.

6. The method for recycling positive electrode materials of waste lithium batteries according to claim 5, characterized in that: In step (1), the hot water is 80-90°C, and the cold water is 10-20°C.

7. The method for recycling positive electrode materials of waste lithium batteries according to claim 5, characterized in that: The concentration of the hydrogen peroxide in step (2) is 30wt%.

8. The method for recycling positive electrode materials of waste lithium batteries according to claim 5, characterized in that: The ammonia concentration in step (3) is 1 mol / L.

9. The method for recycling positive electrode materials of waste lithium batteries according to claim 5, characterized in that: The mass ratio of potassium to sodium in the potassium-sodium alloy in step (5) is 3:

1.

10. The method for recycling positive electrode materials of waste lithium batteries according to claim 5, characterized in that: The conductive agent in step (6) is acetylene black, and its median diameter is 1 to 3 μm.

Citation Information

Patent Citations

  • Method and system for recycling positive poles from waste lithium batteries and carrying out regeneration and repair

    CN110165324A

  • Recovery method of positive electrode material of waste ternary lithium ion battery

    CN111252814A

  • Multi-element metal oxide coated modified nickel-cobalt-manganese ternary positive electrode material as well as preparation method and application thereof

    CN113753972A

  • High-discharge-specific-capacity lithium nickel manganese oxide positive electrode material and preparation method thereof

    CN118658987A

  • Process for Recycling Cobalt and Nickel from Lithium Ion Batteries

    US20220013815A1

Cited By

  • Method for cyclically regenerating ternary precursor, ternary precursor and application

    CN120774478A

  • Preparation method for recycling lithium cobalt nickel manganese oxide battery from quaternary ammonium carboxyl-containing hydroxyl additive

    CN120841581A

  • Separation and recovery method of positive electrode material of waste lithium iron phosphate battery

    CN121005412A